Boundary value problems for impulsive multi-order Hadamard fractional differential equations - Weera Yukunthorn (2018)
© 2015, Yukunthorn et al. In this paper, we study the existence and uniqueness of solutions for impulsive multi-orders Caputo-Hadamard fractional differential equations equipped with boundary and integral conditions. The Banach, Schaefer, and Rothe fixed point theorems and degree theory are used to establish our main results. Examples illustrating the main results are presented.